Propeller Perforator Flaps Used for Hand and Digit Reconstruction: A Systematic Review - Bovill, John; Huffman, Samuel; Cach, Gina; Haffner, Zoe; Deldar, Romina; Abu El Hawa, Areeg A.; Sgromolo, Nicole; Giladi, Aviram M. (Journal of Hand and Microsurgery, 2023)
Background Propeller perforator flaps (PPFs) have increased in popularity due to the freedom in design and ability to cover a variety of defects without sacrificing the major vessels. Present reports of PPFs for upper limb reconstruction have not provided guidance for hand reconstruction, specifically. This study aims to review the current literature and evaluate techniques for use of PPFs in hand reconstruction.Methods A comprehensive literature review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for articles published from 1991 to 2021. The database search was queried for records using appropriate Medical Subject Headings (MeSH) terms. Studies reporting PPFs were limited to English language and excluded lower extremity or upper extremity reconstruction not specific to defects in the hand or digits. Study characteristics, patient demographics, indications, preoperative testing, flap characteristics, flap survival, and complication rates were collected.Results Out of the initial 1,348 citations yielded, 71 underwent full-text review. Ultimately, 25 unique citations were included encompassing 12 retrospective reviews (48%), 3 prospective cohort studies (10%), and 10 case series (40%). In review, 525 patients underwent reconstruction with a total of 613 propeller flaps performed to repair defects of the hand, digits, or both with use of 18 unique flap types. Overall flap survival was 97.8%. Acute wounds accounted for 72.9% of performed reconstructions. The mean flap coverage was 14.7 cm2. Complications occurred in 19.8% of cases, with venous congestion and partial flap necrosis occurring in 5.5 and 6.5% of cases, respectively, leading to a flap failure rate of 2.1%.Conclusion PPFs are a reliable option for hand or digital reconstruction, allowing surgeons to cover a variety of defects without sacrificing local vasculature. Despite nearly a 20% reported complication rate, nearly all flaps with venous congestion and partial flap necrosis included in these articles resolved without the need for secondary intervention, retaining an excellent overall flap survival.
Keywords: autologous reconstruction; finger; flaps; hand; propeller perforator flap